Biochemical Properties and Catalytic Specificity of a Novel Neutral Serine Peptidase Secreted by Fungus Pyrenochaetopsis sp. - Silva, Ronivaldo Rodrigues da [UNESP]; Rosa, Nathalia Gonsales da; Goncalves de Oliveira, Lilian Caroline; Juliano, Maria Aparecida; Juliano, Luiz; Rosa, Jose C.; Cabral, Hamilton (Springer, 2019)
The fungal genus Pyrenochaetopsis has received particular attention because of its different lifestyles, such as numerous plant pathogenic, saprophytic, and endophytic species. Its ability to infect plant cells relies heavily upon secreted peptidases. Here, we investigated the biochemical properties and catalytic specificity of a new serine peptidase secreted by the filamentous fungus Pyrenochaetopsis sp. We found that while this neutral serine peptidase displayed optimal activity at a pH of 7.0 and temperature of 45 degrees C, it tolerated a wide range of pH conditions and temperatures lower than 45 degrees C. Its peptidase activity was depressed by some metallic ions (such as aluminum, cobalt, and copper (II) chloride) and enhanced by others (such as sodium, lithium, magnesium, potassium, calcium, and manganese). Lastly, the enzyme showed the greatest specificity for non-polar amino acids, particularly leucine and isoleucine, and moderate specificity for basic and neutral polar amino acids. It displayed the least specificity for acidic residues.
Keywords: Enzyme; Fungal protease; Proteolytic enzymes; Pathogen; Pyrenochaetopsis